From bedside to the bench: patient-specific hiPSC-EC models uncover endothelial dysfunction in genetic cardiomyopathies - Rabino, Martina; Sommariva, Elena; Zacchigna, Serena; Pompilio, Giulio (Frontiers in Physiology, 2023)
Genetic cardiomyopathies are a group of inherited disorders in which myocardial structure and function are damaged. Many of these pathologies are rare and present with heterogenous phenotypes, thus personalized models are required to completely uncover their pathological mechanisms and develop valuable therapeutic strategies. Both cardiomyocytes and fibroblasts, differentiated from patientspecific human induced pluripotent stem cells, represent the most studied human cardiac cell models in the context of genetic cardiomyopathies. While endothelial dysfunction has been recognized as a possible pathogenetic mechanism, human induced pluripotent stem cells-derived endothelial cells are less studied, despite they constitute a suitable model to specifically dissect the role of the dysfunctional endothelium in the development and progression of these pathologies. In this review, we summarize the main studies in which human induced pluripotent stem cells-derived endothelial cells are used to investigate endothelial dysfunction in genetic-based cardiomyopathies to highlight new potential targets exploitable for therapeutic intervention, and we discuss novel perspectives that encourage research in this direction.Commentato [RM1]: As asked by Reviewer 2, we have replaced reference 7 with a more recent review